The Effect of Self-Care Education on Heart Failure Patients : Literature Review - Devie Dian Wahyuni; Elly Nurachmah; Prima Agustia Nova (Universitas Muhammadiyah Surakarta, 2023)
Heart failure is a heart disease which has an escalating prevalence. Disease conditions that can cause a deterioration in quality of life and even death require further treatment through self-care. Knowledge about self-care can be provided by nurses while the patient is in the hospital even when going home. The purpose of this systematic review is to determine the application of self-care education in heart failure patients to improve self-care knowledge and compliance. The research method used a systematic review design using data bases from ProQuest, EBSCOhost, Scopus, and Science Direct with several keywords used. The results obtained 7 articles that were reviewed after adjusting the inclusion criteria. The results of the study found that the provision of self-care education was able to improve self-care compliance in heart failure patients. The conclusion of this study is that education that is more applicable, interactive and sustainable can improve knowledge and compliance with self-care in heart failure patients.